THE USE OF SOAKING WARM WATER FOR BLOOD PRESSURE REDUCTION IN ELDERLY HYPERTENSIVE PATIENTS - Andita Nugroho, Fiza Paluphi; Widiharti, Widiharti; Suminar, Ervi; Fitrianur, Widya Lita (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: According to a survey conducted by the Indonesian Gerontology Doctor Association in 2022, 37.8% of the elderly population in Indonesia have a history of hypertension. In addition to medication therapy, hypertension can be controlled through non-pharmacological therapy, including to soak the feet in warm water. The purpose of this study is to investigate the use of soaking the feet in warm water to reduce blood pressure in elderly hypertensive patients in Jatikalang, Prambon District.Method: This pre-experimental study uses a one-group of pre-test post-test strategy. The population for this study consists of 46 elderly hypertensive patients. The technique of sampling is purposive, resulting in a sample size of 42 elderly patients. The instruments used are a questionnaire and an observation sheet. Data analysis was by the Wilcoxon test.Results: The systolic blood pressure before soaking the feet in warm water was 140.98 mmHg, and the diastolicof blood pressure was 83.29 mmHg. The results of the analytical test yielded 0.000 (a p-value) for systolic blood pressure, and 0.000 for blood pressure of diastolic.Conclusions: Soaking the feet in warm water has an effect on reducing blood pressure of elderly hypertensive patients. It is hoped that this therapy can be used as an additional treatment for hypertension patients, allowing the community to perform it at home for 15 minutes daily, to lower blood pressure at a low cost.Keywords: Soaking Feet in Warm Water, Blood Pressure, Elderly